The potential and limits of air power in contemporary multinational operations: the case of the UK, Polish and Swedish air forces - Burczynska, Maria Ewa (2019)
This thesis investigates the potential and limits of European air power in multinational operations and assesses how potential problems encountered in the course of multinational cooperation may be overcome. Looking specifically at the cases of the UK, Poland and Sweden, it argues that the benefits European air forces gain from their participation in multinational operations outweigh the challenges they face when involved in that form of military activity. Ultimately, the thesis demonstrates that, considering the significant capability and capacity limitations experienced by European air forces, developing multinational cooperation is essential for maintaining national security and defence of all states involved. Multinational operations have become the dominant form of Western military intervention in the post-Cold War period and this trend is likely to continue. The main objective of the thesis is to provide a deeper understanding of the potential and limitations of European air forces in multinational operations, a subject which has, to date, been understudied. Air power scholarship remains heavily dominated by studies of the US Air Force and US experience in air warfare. As such, the thesis makes a significant contribution to knowledge in providing a systematic study on European air power in multinational operations. The analysis revolves around three case studies – British, Swedish and Polish air power. All three countries experienced similar challenges in building air forces fit for the post-Cold War security environment, but their efforts were also coined by specific geopolitical, financial and political circumstances. Framed within relevant concepts from international relations, strategic studies and military sociology, the analysis is based on the extensive analysis of relevant documentary materials as well as on fieldwork research conducted in all three countries. In its empirical part, the thesis gives a perspective on the state of the British, Polish and Swedish Air Forces in the post-Cold War period, showing that each of them underwent a process of concentration and transnationalisation, adapting them to participation in multinational operations. This took the form of their increased participation in various forms of multinational cooperation ranging from expeditionary military operations, through pooling and sharing initiatives to collective trainings and exercises. All of these processes have raised interoperability and interdependence between European air forces. However, as the thesis also shows, multinational cooperation is complex and poses various problems for the involved air forces which, to large extent, stem from their cultural background. These are inevitable, but may be minimised by even more intensive multinational cooperation.